Answer:
The given expression at p = 5 can be written as:
[tex]4(p^4) > 2p -3[/tex]
Step-by-step explanation:
Here, the given expressions are:
[tex](4p^4 ), (2p-3)[/tex]
Now, substitute the value of p = 5 in both the given expressions, we get:
[tex]4(p^4) = 4(5^4) = 4 (625) = 2,500\\\implies 4(p^4) = 2,500[/tex]
Similarly,
[tex](2p-3) = 2(5) - 3 = 10 -3 = 7\\\implies 2p - 3 = 7[/tex]
So,now comparing both the values at p = 5, we get:
2,500 > 7
[tex]\implies 4(p^4) > 2p -3[/tex]
Hence, the given expression at p = 5 can be written as:
[tex]4(p^4) > 2p -3[/tex]